First record of the leafhopper genus Bambuphaga Ramaiah, Meshram & Dey, 2023 (Hemiptera: Cicadellidae: Deltocephalinae) from China, with description of a new species - Hu, Shangmi; Xing, Jichun (Zootaxa, 2024)
The genus Bambuphaga Ramaiah, Meshram & Dey, 2023 is reported for the first time and a new species, Bambuphaga lanceata sp. nov. is described and illustrated from China. A key is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).